O ensino de história nos anos iniciais do ensino fundamental I: a cachaça como “lugar de memória” no município de Abaetetuba/PA - FERREIRA, Erick Fernando Figueiredo (2023)
This article approaches the theme of teaching History and its methodologies, which according to the Annales school, are important tools that help the educator. Having bibliographical research as a methodological indicator, this writing sought to highlight the importance of local culture through the appreciation of the memory of the inhabitants of the Municipality of Abaetetuba/PA, indicating Cachaça as a “place of memory”. As a theoretical foundation, Silva and Silva (2009), Bittencourt (2004) and Nora (2012) were mainly used, who postulate in their works about the historical turn and the influence of this event on the work of historians. As final considerations, the article emphasizes the traditionalist view regarding the teaching of history in schools, which is something negative, since the records of historical events are told by great characters and only their deeds are shown, therefore, the importance and necessity of valuing memory and local culture, in order to keep alive the history that surrounds and collaborates for the construction of the citizen of Abbaetetubo, in addition to pointing to na eminent professional deconstruction that aims at na opening for the insertion of new methodological procedures for the teaching the discipline of History.